Animal Bones from an Early Bronze Age Midden Layer at Torslev, Northern Jutland - Nyegaard, Georg (Journal of Danish Archaeology, 1993)
Animal Bones from an Early Bronze Age Midden Layer at Torslev, Northern Jutland